Evaluation of surface roughness of the bracket slot before and after burning - Raudhatul Jannah; Bergman Thahar; Endah Mardiati; Ida Ayu Evangelina (Majalah Kedokteran Gigi Indonesia, 2018)
Slot bracket base is one important element to enable sliding movement of the archwire. Bracket reconditioning by means of burning changes the surface roughness of slot bracket base. The heat above 450 °C shows microstructure changes of the slot surface. On this basis, the present study aims to evaluate surface roughness changes of the slot bracket base before and after reconditioning by means of burning. Sixteen premolar brackets standard edgewise were divided into two groups each consisting of eight brackets. These two groups were tested at three different points using Scanning Electron Microscopy (SEM), with 3000 times of magnification. Subsequentl,group A was burned for 5 seconds (approximately 450 °C) and group B was burned for 10 seconds(approximately 643 °C). After treatment,these two groups were tested for the second time using Scanning Electron Microscopy (SEM), with 3000 times magnification and the images were analyzed using a discrete scale quantitative classification. Afterwards, the data were analyzed using ANOVA (p≤0.05) and post hoc analysis. The result showed that surface roughness of the slot bracket base burned for 10 seconds experienced more significant change than that of bracket burned for 5 seconds and that of the control bracket(p≤0.05).Bracket reconditioning using burning either for 5 to 10 seconds change the surface roughness of the slot bracket base.